MEDIA’S ROLE ON WOMEN CONCEPT OF BEAUTY - Ishmiyatillah, Ishmiyatillah (Jurnal Ilmiah IKIP Mataram, 2018)
This thesis aims to study the images of women’s ideal through media, in this case American Fashion movies. The study is performed based on these formulated problems: 1) How women and women’s appearance are represented in American fashion movies? 2) How do the women’s representations in the movies reveal American cultural myth about beauty and what attitude do the movies have toward beauty myth?. The object of study is three box office fashion movies in the US: The Devil Wears Prada, Sex and the City I, and Sex and the City II.. The movies are examined using Barthes’ semiological approach in which any materials of speech or communication in media (pictures, written and spoken words) are regarded as signifying certain concept or idea.